Effects of environmental and carbon taxation: A literature review - Angela Köppl; Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2021)
In view of the challenges posed by climate change and the increase in climate targets by 2030 in the EU, as well as Austria's goal of achieving climate neutrality by 2040, the question of effective climate policy instruments is gaining in importance. The pricing of CO2, for instance in the form of a carbon tax, and the question of its effects are therefore attracting increasing attention in the academic as well as economic and environmental policy debate. The paper provides a detailed overview of the theoretical and empirical literature on the effects of carbon taxes. The focus is on the most important impact dimensions of carbon taxes: environmental effectiveness, effects on important macroeconomic variables (especially growth and employment), effects on innovation and competitiveness, distributional effects, and public acceptance.
Keywords: H23; Q54; Q58; 330; Carbon Tax; Environmental Taxation; Double Dividend Hypothesis; Distributional Effects; Climate Policy; Price-based Instruments